A STUDY ON INFECTIOUS DISEASE BURDEN AND ASSESSMENT OF ADVERSE DRUG REACTIONS AMONG TYPE- II DIABETES MELLITUS SUBJECTS - Mathew, Adarsh; DR, Bharathi; Siddiq, Abubaker; Alex, Akza K; M, Tejaswini S (Journal of Biomedical and Pharmaceutical Research, 2019)
Introduction: People with diabetes are more prone to development of infections. Elevated blood sugar levels enervate the patient’s immune system and make the patient vulnerable to infections.Assessing the prescription patterns assure quality medical care by providing feedback to the prescribers.Objectives: To assess the prevalence and the prescription pattern of antibiotics in infections associated with type II diabetes mellitus along with their quality of life. To assess the Adverse Drug Reactions associated with treatment of type-II diabetes mellitus.Materials and Methods: This prospective observational study was conducted in the General Medicine Department of Basaveshwara Medical College Hospital and Research Centre, Chitradurga for a period of 10 months.Results: In this study, a total of 300 diabetic subjects were included, out of which, 192 subjects were having infectious diseases. This study reveals association between infection and diabetes with a prevalence rate of 64%. The most commonly prescribed antibiotic was found to be ceftriaxone. The quality of life of the diabetic subjects associated with infections was found to be displeasing when assessed with a validated questionnaire.Conclusion: The study shows a higher rate of prevalence of infectious disease among diabetic subjects. It is suggested to conduct more studies on this topic.Keywords: Diabetes mellitus; Infectious diseases; Adverse drug reactions; Burden of disease.